Determination of parameters Belleville Springs for Tsubaki Disco - 冯澄宙; 林卫东 (Jixie chuandong)
In ordet to obtain a good effect of Disco properties, msed on analysihg load deflection characteristics of Belleville springs,Parameters of Belleville springs for Disco is determined in this paper.